EMPOWERING PARENTS OF CHILDREN WITH SPECIAL EDUCATION NEEDS: LEVERAGING GENERATIVE AI TO ALLEVIATE STRESS AND ENHANCE LEARNING OUTCOMES - Wai Hung Ip (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Raising children with special education needs (SEN) in Hong Kong poses significant challenges for parents, who must juggle roles as educators, therapists, and caregivers. The city’s competitive academic culture intensifies the tension between providing unconditional support and meeting rigorous academic expectations. Despite the increasing prevalence of SEN children, there are no parental support programs that integrate innovative technologies to address these dual burdens. This study introduces a novel parental training program that leverages generative artificial intelligence (GenAI) tools to empower parents as self-directed designers of AI-supported learning tasks. The program aims to reduce parental stress, enhance self-efficacy, and improve children’s learning outcomes through transformative learning processes. A pilot study will be conducted in primary schools across Hong Kong, involving 100 parents over five weeks. Using a mixed-methods approach, the study will evaluate changes in parental stress, self-efficacy, and children’s academic performance. The findings are expected to demonstrate the potential of GenAI to provide personalized learning support for children while offering real-time guidance and stress management for parents. This research highlights the transformative potential of GenAI in reducing parental stress and contributes to global efforts to integrate AI into educational and caregiving practices, offering scalable solutions for families of SEN children.